ANALYSIS OFRISK FACTORS INCREASE BLOOD PRESSURE IN THE TEXTILE INDUSTRY WORKERS - -, Sumardiyono; -, Hartono; Probandari, Ari; Setyono, Prabang (Universitas Muhammadiyah Semarang, 2017)
The risk factors for high blood pressure are industrial noise exposure, age, body mass index, and length of exposure to noise. Exposure to noise is often found in industrial workers. Therefore, workers are at increased risk for high blood pressure. The purpose of this study is to investigate the association of noise level, age, body mass index, and length of exposure to noise with blood pressure on textile industryworkers. This study was observational research with cross sectional design. The population were textile industry workers in Surakarta. The sample selection used purposive random sampling. Inclusion criterias were women, length of working at least one year, less disciplined use ear protection equipment.The total samples were 245 peoples.Statistical analysis used bivariate correlations and multiple linear regression. There was an association between all variables with blood pressure.However, on multiple linear regression test, length of exposure to noiseexclused. Variables that associated with systolic blood pressure were the noise level (p=0.026), age (p=0.002), body mass index (p=000). Variables thatassociated with diastolic blood pressure were the noise level (p=0.011), age (p=0.15), body mass index (p=0.000). The risk factors for high blood pressure among industrial worker are the noise level, age, and body mass index. Keyword: blood pressure, textile industry workers